First Report of Citrus Leaf Blotch Virus on Nagami Kumquat in Turkey - Fidanci Avci, Busra (Plant disease, 2024)
Kumquat, known as the smallest of citrus fruits, has seen an increase in the number of commercial orchards in recent years. In May of 2022, a PCR-based survey for citrus virus diseases was conducted in commercial Nagami kumquat (Fortunella margarita (Lour.) Swingle) orchards in the Cukurova region of Turkey. During the survey, five trees with bud union disorder symptoms were found in two different kumquat orchards in the Erdemli district of Mersin province. Young leaf samples from the five trees showing bud union disorder symptoms and two symptomless trees were collected from 6-year-old kumquat. Common citrus viruses and viroids, such as citrus psorosis virus, citrus exocortis viroid, and hop stunt viroid, were not detected in PCR tests performed on all collected samples. The samples were also tested for citrus leaf blotch virus (CLBV; genus Citrivirus, family Betaflexiviridae), a virus associated with a bud union crease in kumquat (Vives et al.2001). Total RNA was isolated from collected leaf samples using the RNeasy Plant Mini Kit (Qiagen, USA). In the RT-PCR assay, two separate specific primer pairs were used to determine the presence of CLBV. The coat protein gene (CP), was amplified with primers KU-18 (5'-TTAAGATTACAGACACGAAGG- 3') and KU-19 (5' CTGTTTTTGAATTTTGCTCG-3'), and the RNA-dependent RNA polymerase gene (RdRp) was amplified with KU-27(5'-GATGCAAGCCAGGATGAATAC-3') and KU-15 (5'-CAGACACTCCAAGACCTTTCC-3') primers (Vives et al. 2002). All of symptomatic samples yielded amplicons of the expected size (456-bp RdRp and 438-bp CP). No amplicons were obtained from symptomless samples. Two PCR products were sequenced to confirm their identity by direct sequencing (GenBank accession no: OQ718432, OQ718433, PP726107, PP726108). Consensus sequences of these two genes showed 96% and 97% nt identity with CP and RdRP genes of the CLBV sequence in GenBank (MT038390, EU857539), respectively. For biological indexing, four RT-PCR-positive samples were used as inoculum sources. Four of Etrog citron (C. medica) and four of Dweet tangor (C. tangerina) seedlings were graft-inoculated for each source, and two seedlings for each cultivar were used as a negative control. Two months later, chlorotic blotching symptoms were observed on Dweet tangor leaves. Six months later, Etrog citron exhibited stem pitting symptoms. None of the negative control seedlings developed any symptoms. RT-PCR was performed to confirm the presence of CLBV in the virus-inoculated seedlings, and amplicons of the expected sizes (456-bp RdRp and 438-bp CP) were obtained. To the best of our knowledge, this is the first report of the CLBV infection in citrus in Turkey. CLBV is thought to have originated from infected grafting material in the country, although it is not known where it may have originated. Further research is needed to determine the distribution of CLBV and its potential to impact commercial citrus production in Turkey